2014
DOI: 10.1177/0194599814555837
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic Yield of MRI for Pediatric Hearing Loss: A Systematic Review

Abstract: Objective To perform a systematic review to analyze the diagnostic yield of magnetic resonance imaging (MRI) for pediatric hearing loss, including comparison to computed tomography (CT) and subgroup evaluation according to impairment severity and specific diagnostic findings (cochlear anomalies, enlarged vestibular aqueduct, cochlear nerve abnormalities, and brain findings). Data Sources Pubmed, EMBASE, and the Cochrane library were assessed from their inception through December 2013. Manual searches were al… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
29
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(29 citation statements)
references
References 80 publications
0
29
0
Order By: Relevance
“…Given the high degree of discordance between imaging finding interpretations in our series, we further recommend that these children be imaged and evaluated at centers with a neuroradiologist experienced with the complexities of these children. Our data also show that a dual imaging workup, e.g., HD CT and sMRI, allows acquisition of the most complete information on the status of the inner ear and nerve, as others have suggested [Westerhof et al, 2001;Sakina et al, 2006;Adunka et al, 2007;Miyasaka et al, 2010;Vlastarakos et al, 2010;Kachniarz et al, 2015]. In a comparison of CT with MRI for detecting clinically significant abnormalities, one imaging modality was not able to identify an abnormality detected by the other modality in 31% of the cases [Simons et al, 2006].…”
Section: Imaging Recommendationsmentioning
confidence: 42%
“…Given the high degree of discordance between imaging finding interpretations in our series, we further recommend that these children be imaged and evaluated at centers with a neuroradiologist experienced with the complexities of these children. Our data also show that a dual imaging workup, e.g., HD CT and sMRI, allows acquisition of the most complete information on the status of the inner ear and nerve, as others have suggested [Westerhof et al, 2001;Sakina et al, 2006;Adunka et al, 2007;Miyasaka et al, 2010;Vlastarakos et al, 2010;Kachniarz et al, 2015]. In a comparison of CT with MRI for detecting clinically significant abnormalities, one imaging modality was not able to identify an abnormality detected by the other modality in 31% of the cases [Simons et al, 2006].…”
Section: Imaging Recommendationsmentioning
confidence: 42%
“…The bony margins of the stenotic/atretic canal can be demonstrated by CT. The bony deformity may compress the vestibulocochlear nerves (VCNs) [2,12,18,19] .…”
Section: Discussionmentioning
confidence: 99%
“…Three types of vestibulocochlear nerve hypoplasia and aplasia can be distinguished, as follows: type 1 displays stenotic IAC and VCN aplasia; type 2A involves a common VCN with aplasia/hypoplasia of the cochlear branch and labyrinthine malformation; type 2B shows normal labyrinthine structures [2,12,18] . Also, facial nerve hypoplasia may be seen with middle ear anomalies.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Systematic reviews concluded that the diagnostic yield of imaging studies is approximately 30% for CT and 26% for MRI, respectively. 40,41 Imaging studies provide important information about anatomic variation in patients and can guide surgical planning for cochlear implantation; however, decision regarding timing of imaging must take into account risks attributable to either radiation exposure or sedation. If no significant management alterations would derive from imaging findings, one may consider deferring imaging until the child is old enough to undergo MRI without sedation, unless a non-sedated MRI protocol is available.…”
Section: Basic Algorithm For Evaluation Of Congenital Sensorineuramentioning
confidence: 99%